Towards a Plural Olympic Studies Agenda: Contesting Orientalism Through Arab Sport Narratives - Mahfoud Amara (7236599) (2025)
This paper critically explores the Arab world’s engagement with the Olympic Movement and global sport through a postcolonial and cultural lens. It examines how colonial legacies shaped early sport structures in North Africa and the Middle East, and how these were later re-appropriated in the service of national identity, Islamic values, and regional solidarity. From the Pan-Arab and Islamic Games to the strategic use of sport mega-events by Gulf states, the paper analyzes how sport has become a vehicle for both political assertion and soft power projection. It challenges dominant Orientalist narratives by foregrounding the agency of Arab athletes, particularly women and diasporic figures, in reshaping global perceptions. The paper argues for a pluralized approach to Olympic and sport studies that recognizes the Arab region not merely as a recipient of global sport models, but as an active contributor to evolving meanings of modernity, inclusion, and international legitimacy. Other Information Published in: Asian Journal of Sport History & Culture License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/27690148.2025.2530592